The distribution of hepatitis C virus genotypes in patients with hepatocellular carcinoma - Bakır, Ayfer; Karabulut, Nuran; Alaçam, Sema; Bakır, Barış; Ağaçfidan, Ali (Asian Journal of Medical Sciences, 2019)
Background: Hepatic cirrhosis develops within 20-30 years in approximately 20% of individuals chronically infected with hepatitis C virus (HCV). Aims and Objective: This study aimed to determine the distribution of HCV genotypes in patients with HCV-associated HCC in our region and thus to contribute to the epidemiology of HCV. Materials and Methods: HCC patients referred to the virology laboratory for HCV genotype identification between January 2013 and April 2018 were included in this study. Genotyping of HCV was performed by a commercial reverse hybridization line probe-based assay. Results: Seventeen patients who were diagnosed with HCC and whose HCV genotypes were analyzed were included in this study. Genotype 1 was detected in all 17 patients with HCC. When evaluating subtypes of genotype 1, genotype 1b was detected in 16 (94%) of the patients. The HCV subtyping in one patient (6%) could not be performed. Conclusion: As a result, genotype 1b, one of the major risk factors for HCC, was detected in 94% of the patients included in this study. This study, consistent with the literature, shows a high association between the development of HCC and genotype 1b in patients with chronic HCV.